Strut and tie modeling of reinforced concrete corbel - Jong, Jeffri (2015)
The present investigation examines analytically the behavior and ultimate shear strength of reinforced concrete corbels with varying outer depth to total depth (k/h) ratio. The reinforced concrete corbel design provision by Eurocode 2 Annex J is also examined for its quantity and rationale of the placement of different types of stirrups, namely closed horizontal and vertical links. Academic papers from Hwang et al, Aziz et al and Zeller, W. are used to further justify this analysis. The results indicate that with increasing k/h ratio, corbel experiences an increase in ultimate shear strength. This can be explained through more deformation resistance of corbel that has higher k/h ratio. After further analysis, it was found that Eurocode 2 Annex J provides adequate reinforcement for cracking control as well. Closed horizontal links are provided for corbel with shear span to total depth ratio less than 0.5, because of its crack pattern, which is closed to vertical. Closed vertical links are provided for corbel with shear span to total depth ratio of more than 0.5, because cracks are formed at an angle of 45 degrees of more and hence, stirrups that are perpendicular to the cracks are more effective, and hence the use of vertical links. The results show that Eurocode 2 provision in links stated in Annex J for corbel is indeed sufficient and reasoned